The controversy about “Scar Literature” and the literary policy of the PRC in the late 1970s — mid-1980s - A. N. Korobova (Шаги)
“Scar Literature” (伤痕文学) was a mainstream movement in Chinese literature in the late 1970s — mid 1980s. It dealt mainly with the fate of the younger generation, which under the influence of political propaganda had abandoned genuine human values, with the tragic fates of the intelligentsia, and with the betrayal of loved ones. “Scar Literature” also used to describe the lawlessness that occurred in prisons and labor camps. In the first years after the “cultural revolution”, the controversy about “Scar Literature” was concentrated mainly around the themes and the name of the trend, almost without discussing the literary aspects themselves. Despite the weakening of ideological control after the end of the “cultural revolution”, the name “Scar Literature” was not approved by the authorities and even had a negative connotation: in 1979, articles appeared in the Chinese press, the authors of which opposed the use of the expressions “Scar Literature” and “exposure literature”, urging writers not to focus on the dark sides of the past and pointing out the high reputational risks for the CPC. In a broader sense, the polemics about “Scar Literature” were a dispute about a possible reassessment of the relationship between literature and politics, and the essence of realism as a creative method. After several decades, when the ideological tension regarding the “cultural revolution” has decreased, “Scar Literature” continues to arouse interest — but now as a literary representation of experiencing psychological trauma.